Phenol-derived products from fast pyrolysis of organosolv lignin. (November 2020) - Soongprasit, Kanit; Sricharoenchaikul, Viboon; Atong, Duangduen
Abstract: Lignin is the largest aromatic bio-polymer feedstock with a huge potential of being refined for aromatic chemical platform and building block. Organosolv process for lignin extraction has a low impact on the environment due to its low chemical requirement, the absence of sulfur, and as it is more practical for chemical recovery. Therefore, refinement of extracted lignin to valuable molecular compounds such as purified lignin and its derivative is the key success for biorefinery industry. In this study, sugarcane bagasse from a local sugar manufacturer in Thailand, noted as BG-lignin, was selected as feedstock for lignin extraction using ethanol and water. The chemical composition of this lignin was slightly different than that of commercially available organosolv lignin, noted as Comm-OS-lignin, in that BG-lignin has more combustible constituents (volatile organic compounds and fixed carbon) of 96.14% and low ash content of 0.09%. The chemical structure of BG-lignin contains a higher number of aliphatic hydrocarbon and aliphatic hydroxy side chains than Comm-OS-lignin, as confirmed by the FT-IR and 1 H-NMR analyses. The study on fast pyrolysis of lignin, using Py-GCMS technique, found 2, 3-dihydrobenzofuran as a major constituent at any tested pyrolysis temperature. H-unit, G-unit, and S-unit are distributed in resemble fraction with a H ∕ G ∕ S ratio of 1 ∕ 1 ∕ 0 . 7 and 0 . 8 ∕ 1 ∕ 1 for Comm-OS-lignin and BG-lignin, respectively, at pyrolysis temperature of 400–600 °C, except for H-unit which was enhanced at 700 °C to 28.82% of Comm-OS-lignin and 29.66% of BG-lignin. At a temperature of 400–600 °C, phenolic selectivity of pyrolyzed products, mainly methoxy phenol (Ph-OCH3 ) and alkylated phenol (R-Ph-OCH3 ), was done. A higher pyrolysis temperature of 700 °C led to the elimination of aromatic side group and is more favorable in alkyl phenol (R-Ph) and phenol selectivity. However, reduction of the phenolic compound was observed with a higher temperature due to thermal fragmentation of the C–C linkage in the aromatic structure. Products selectivity related to lignin feedstock and pyrolysis temperature could be applied as a conceptual guideline for conducting further study of chemical upgrading process to obtain high-value biochemical products.